A study of correlation of pre-operative fine needle aspiration cytology and ultrasonography with post-operative histopathology in thyroid swellings - Parameshwar Narayanakar, Rajkumar; Govinda Shetty, Darshan Saligrama (International Surgery Journal, 2020)
Background:Diseases of the thyroid gland can be due to inflammatory and neoplastic causes. Many diagnostic tests like ultrasound, thyroid nuclear scan and fine needle aspiration cytology (FNAC) are available for their evaluation. Histopathologically, they can be adenomas, colloid nodules, cysts, infectious nodules, lymphocytic or granulomatous nodules, congenital abnormalities or hyperplasia, or various types of malignancy. It is therefore crucial to have a clear diagnostic approach to ensure patients are managed appropriately and are not over or under-treated. Present study was done to evaluate FNAC and ultrasonography (USG) as a diagnostic method in thyroid swellings and to plan surgery accordingly. Methods: A prospective observational study was conducted among 60 adult patients undergoing thyroid surgery at Victoria and Bowring and Lady Curzon Hospital. They were investigated with FNAC and USG of thyroid, and were subjected to surgery and subsequent histopathological examination. The histopathological examination reports were correlated with the findings of FNAC and USG in order to evaluate their findings by statistical methods. Results:The sensitivity and specificity of FNAC was 87.5% and 98% respectively. All malignant lesions on FNAC were confirmed by histopathology indicating its excellence. Therefore FNAC helps in planning the correct management and avoids second surgery. And the sensitivity and specificity of USG was 75% and 86% respectively. Therefore combination of both FNAC and ultrasonography will improve the diagnostic accuracy to higher level and helps in better management. Conclusions:FNAC has high sensitivity and specificity, so it is closest to ideal test. However, a combination of both FNAC and ultrasound will give desirable results and so that we can avoid mismanagement.